KNOWLEDGE, ATTITUDE AND PRACTICE OF PRIVATE PRACTITIONERS REGARDING TB-DOTS IN A RURAL DISTRICT OF SINDH, PAKISTAN - Ahmed, Mubashir; Fatmi, Zafar; Ali, Sajid; Ahmed, Jamil; Ara, Naseem (Journal of Ayub Medical College Abbottabad, 2009)
Background: Tuberculosis is prevailing in both urban and rural areas of Pakistan. Knowledge, attitude and practice (KAP) of private practitioners (PPs) regarding tuberculosis management have been reported only in urban areas of Pakistan. This survey was conducted for the first time in a rural area of Sindh, Pakistan. Methods: This survey was conducted in January 2007 at Thatta, a rural district of Sindh, Pakistan. Study subjects were twenty-two allopathic qualified (MBBS) doctors of district Thatta, who were practicing in private setups for at least last one year. Before TB-DOTS training PPs had filled the KAP questionnaire regarding tuberculosis (TB) diagnosis and management through DOTS. Survey data was analysed through SPSS version 11.05 software. Results: On average, five TB suspects per month were seen by each PP. Only 14% of PPs advised sputum microscopy solely for pulmonary TB diagnosis, while 86% of PPs used different combination of tests (chest x-ray/sputum microscopy/ESR/tuberculin test) for TB diagnosis. Over 40% PPs did not prescribe TB treatment regimen according to TB-DOTS category. Majority PPs (85%) did not follow the treatment through sputum microscopy and instead relied on clinical improvement and x-ray clearance. Nearly 60% of TB patients at PPs clinic did not show compliance to the TB treatment and none of PPs were following the retrieval of default cases. Conclusions: A gross lack of PPs knowledge and right practice regarding TB diagnosis and management through DOTS was identified and needed to be addressed through providing DOTS training. Keywords: Tuberculosis, DOTS, private practitioners, knowledge, practice